Post a New Question

algebra

posted by .

2x/x-4 + 4/x-3 = 8/x^2-7x+12

  • algebra -

    did you notice that
    x^2 - 7x + 12 = (x-4)(x-3) which happen to be denominators of the first 2 terms?
    So the LCD is (x-4)(x-3)
    Multiply each term by that LCD to get

    2x(x-3) + 4(x-4) = 8
    2x^2 + 4x - 30 = 0
    x^2 + 2x - 15 = 0
    (x+5)(x-3) = 0
    x = -5 or x = 3
    BUT x=3 would make the expression undefined,
    so
    x = -5

Answer This Question

First Name
School Subject
Your Answer

Related Questions

More Related Questions

Post a New Question